Routledge Handbook of Sport Governance (Routledge, 2020)
The Routledge Handbook of Sport Governance is a comprehensive and authoritative survey of the wide range of issues shaping sport governance. It considers the evolution of the sport industry from a largely amateur, volunteer-driven sector into the globalised business that it is today and examines how professionalisation has fundamentally shifted the governance landscape for sport organisations and all those working within sport.